Tobacco use and its relationship with health complaints among employees of Kermanshah province, Iran - Nahid Khademi; Mehran Babanejad; Farid Najafi; Mohammad Reza Nikbakht; Behrooz Hamzeh; Nasrin Mohammadi (International Journal of Preventive Medicine, 2016)
Background: Identifying the pattern of tobacco use and its related factors in employees is crucial. This study aimed to investigate the pattern of tobacco use and its related factors in employees of Kermanshah Province, Iran. Methods: In 2012, 7129 employees were investigated in a cross-sectional study using the census method. Data on tobacco use and on several chronic diseases obtained using a standardized questionnaire on noncommunicable diseases risk factors of the World Health Organization through face-to-face interviews. Statistical analysis was performed based on the Chi-square test and multivariate logistic regression. Results: In general, the prevalence of tobacco use, smoking cigarettes, and smoking waterpipe was 9.9%, 8.9%, and 1.2% among the employees, respectively. Tobacco use was significantly higher in the age group over 40 (14.0%), in male gender (13.3%), in married individuals (10.8%) and in those with diploma and lower degree (16.4%), (P < 0.001). At the individual level, the odds ratio of tobacco use was 1.5 (95% confidence interval [CI]: 1.2-1.8) in hypertensive, 1.8 (95% CI: 1.2-2.6) in diabetic employees and 1.7 (95% CI: 1.3-2.3) in those with heart diseases, compared to healthy individuals. After adjusting for age, gender, marital status and educational level, there was not any significant relationship between tobacco use and health complaints and only the demographic variables remained significant. Conclusions: Preventive public health policies are mandatory especially in younger ages and male employees to promote their knowledge on disadvantages of tobacco use.